Student Scientific Group Work Within the System of Professional Adaptation - Trefanenko, Iryna; Hrechko, Svitlana; Soloviova, Olga (My University, 2020)
In the present article we discuss the role of problem-based learning, namely games in out-ofclass student scientific research. The authors analyze means and methods of conducting this type of scientific research within the framework of scientific society of Internal Medicine, Clinical Pharmacology and Occupational Diseases department. Thus students get assistance with broadening their concept of the world, developing skills to apply theoretical knowledge and modern scientific research methods in practical context, which are of great importance for acquiring professional skills and further scientific research of students after University graduation.
Keywords: games; problem-based learning; student scientific society